Exploring on transitional living spaces to improve quality of life of fishermen in Malaysia - Mazyoona, Aminath; Zairul, Mohd; D’Silva, Jeffrey Lawrence (Human Resource Management Academic Research Society, 2023)
Transitional living spaces are considered to be a short term accommodation arrangements that are designed to help individuals or families who are experiencing a period of transition or instability. Such living spaces are expected to lead them towards a more stable setting of living condition. However, the current architectural approach towards transitional living spaces or accommodations do not address properly to the needs of targeted user and are usually designed universally. Therefore, instead of improving the living quality of the users, due improper spatial quality of such spaces could even lead to lowering their standard of living. Hence, the aim of this research is to explore on the living condition of fishing communities in Malaysia and produce a design framework on designing transitional living spaces for them. This research is based on ethnography of qualitative methodology uses literature review. The results show a design framework on designing suitable transitional living spaces for fishermen in Malaysia. This framework will help to increase awareness on importance of transitional living spaces for fishermen which would contribute to improve quality of fishermens livelihood. This produced framework could be used for transit living spaces for middle aged fishermen.